German medical data sciences: a learning healthcare system : proceedings of the 63rd annual meeting of the German Association of Medical Informatics, Biometry and Epidemiology (gmds e.V.) 2018 in Osnabrück, Germany - GMDS 2018 - Hübner, Ursula (Studies in health technology and informatics, 2018)
Advances in digital and information technology have meant that medical informatics and its associated fields are of ever-increasing importance in the modern healthcare environment. This book presents selected papers from the 63rd annual conference o...